Pengaruh Ukuran Perusahaan, Profitabilitas dan Kepemilikan Institusional Terhadap Kebijakan Utang pada Perusahaan Batu Bara - Rohmatul Alysa; Venda Nur Afandi; Dea Shafira; Dwi Ermayanti Susilo (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2023)
The purpose of this study was to examine the effect of company size, profitability, and institutional ownership on the debt policies of coal companies listed on the Indonesia Stock Exchange in 2020-2021. The study utilizes a combination of quantitative and descriptive analysis methodologies. The sample consists of 19 coal companies with a predetermined time. The study analysis includes tests of classical assumptions, equations for multiple linear regression, and hypothesis testing with a significance level of 5%. Data analysis was performed using SPSS software. The test results (t-test) prove that: (1) company size has a significant negative effect on debt policy; (2) profitability has no effect on debt policy; (3) Institutional Ownership has a significant negative effect on debt policy.